2021
DOI: 10.9734/arja/2020/v13i430112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exogenous Hormonal Stimulation on the Metabolic Partition between Plant Growth and Rubber Production of Hevea brasiliensis Clones According to the Class of Metabolic Activity in Cote d'ivoire

Abstract: Aims: In order to achieve a good and sustainable harvest of Hevea brasiliensis rubber, the effect of exogenous hormonal stimulation on the metabolic partition growth-production of clones according to the class of metabolic activity was made. Place and Duration of Study: The study was conducted for 9 years in the San-Pedro region in south-west Ivory Coast, precisely in the experimental industrial plantations of the former HEVEGO, now Southwestern Agricultural Civil Society Société (SCASO). Methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In relation to TPD prevention, RSH behaviour is still not fully understood. In some studies, RSH content was reported to be stable or increase with harvesting stress ( Herlinawati and Kuswanhadi, 2012 ; Rukkhun et al., 2020 ; Irénée et al., 2020 ), or decreased ( Dian et al., 2016 ; Gohet et al., 2019 ). This inconsistency leads to difficulties in interpretating RSH data and calls for a comprehensive study of RSH dynamics in different stress types and levels.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to TPD prevention, RSH behaviour is still not fully understood. In some studies, RSH content was reported to be stable or increase with harvesting stress ( Herlinawati and Kuswanhadi, 2012 ; Rukkhun et al., 2020 ; Irénée et al., 2020 ), or decreased ( Dian et al., 2016 ; Gohet et al., 2019 ). This inconsistency leads to difficulties in interpretating RSH data and calls for a comprehensive study of RSH dynamics in different stress types and levels.…”
Section: Introductionmentioning
confidence: 99%